Effect of levamisole on Mycobacterium leprae in mice. - Shepard, C C (1977)
Levamisole, an antihelminthic drug that is capable of enhancing immune responses in mice and in humans, was tested in experimental Mycobacterium leprae infections in mice by a number of schedules. Intermittent schedules were used, and administration of the drug was started (i) around the time of inoculation with M. leprae, (ii) when the M. leprae population was approaching the plateau level, (iii) after the onset of the plateau phase, or (iv) after BCG vaccination 28 days following the inoculation with M. leprae. No effect of drug could be discerned with any of the schedules.